Study of W boson production in association with beauty and charm - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The associated production of a W boson with a jet originating from either a light parton or heavy-flavor quark is studied in the forward region using proton-proton collisions. The analysis uses data corresponding to integrated luminosities of 1.0 and 2.0 fb−1 collected with the LHCb detector at center-of-mass energies of 7 and 8 TeV, respectively. The W bosons are reconstructed using the W→μν decay and muons with a transverse momentum, pT, larger than 20 GeV in the pseudorapidity range 2.0<η<4.5. The partons are reconstructed as jets with pT>20 GeV and 2.2<η<4.2. The sum of the muon and jet momenta must satisfy pT>20 GeV. The fraction of W+jet events that originate from beauty and charm quarks is measured, along with the charge asymmetries of the W+b and W+c production cross sections. The ratio of the W+jet to Z+jet production cross sections is also measured using the Z→μμ decay. All results are in agreement with Standard Model predictions.
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Gesehen am 02.08.2021